Komunikasi Identitas Destinasi dalam Wisata Sejarah Lintas Zaman: Representasi Tokoh Bangsa dan Wali Songo di Surabaya - Rahmadani Rafik; M. Ryan Refano; Mohammad Insan Romadhan (CV. ITTC INDONESIA, 2025)
This study aims to examine how destination identity communication is constructed through the representation of national heroes and Wali Songo figures within the context of historical tourism in Surabaya. The city possesses a rich historical narrative, encompassing the era of Islamic dissemination by Wali Songo as well as the struggle for independence led by national figures. However, these two streams of representation are often separated in destination communication strategies—whether through visual media, narrative frameworks, or visitor experiences. This research employs a qualitative approach using a case study method, involving field observations at historical tourism sites (the November 10th Museum, Heroes Monument, and the Sunan Ampel Complex), in-depth interviews with site managers, tour guides, and community leaders, as well as analysis of promotional and visual media documentation. The findings indicate that destination communication tends to segregate religious narratives (Sunan Ampel) from nationalist ones (Bung Tomo and other independence figures), resulting in a fragmented city identity. Visual, audio, and digital representations are curated thematically without linking the historical continuity across time periods.